KERJA SAMA INDONESIA DENGAN JERMAN DIBIDANG PENGELOLAAN HUTAN DAN PERUBAHAN IKLIM MELALUI FORESTS AND CLIMATE CHANGE PROGRAMME (FORCLIME) PERIODE 2017-2020 - Dewi Arun Putri Saraswati (2023)
The issue of climate change is currently on the global political agenda because the impact felt by these environmental threats is very serious, so it becomes a special discussion for countries in the world. Indonesia has ratified the Paris Agreement and Indonesia has a target of NDCs to reduce GHG emissions by 29% nationally and 41% with international assistance. The forestry sector is one of the biggest contributors to GHG emissions caused by deforestation. So with that, Indonesia is establishing bilateral cooperation with Germany in the field of forest management and climate change through the Forests and Climate Change Program (FORCLIME), which is currently running its third phase, namely the 2017-2020 period. To discuss these issues, the researcher in this case uses a descriptive qualitative method which aims to describe the facts related to the problems studied with the theory of bilateral cooperation, national interest and Green Politics Theory (GPT). From the results of the research that has been carried out, it shows that the cooperation between Indonesia and Germany through FORCLIME in this third phase, namely 2017-2020, has almost entirely been implemented. In addition, the deforestation rate in the 2017-2020 period has been successfully reduced so that this has an impact on reducing Indonesia's national GHG emissions. Meanwhile, FORCLIME has also been able to increase public awareness to actively participate in forest management and create pro-environmental and pro-people economic development. So, it can be said that the overall FORCLIME cooperation for the 2017-2020 period between Indonesia and Germany has been going well.